1985
DOI: 10.3147/jsfp.20.229
|View full text |Cite
|
Sign up to set email alerts
|

Location of Vibrio anguillarum in tissues of infected rainbow trout (Salmo gairdneri) using the fluorescent antibody technique.

Abstract: Rainbow trout (Salmo gairdneri) were injected intraperitoneally (IP) or waterborne infected with Vibrio anguillarum, strain LS-174. Every three hours for 48 h, three fish were sampled and fixed for histological examination. The progression of the infection and the fate of the invading pathogen was determined by staining sections with anti V. anguillarum fluorescein-labeled rabbit immunoglobulin G (IgG). The tissue location of the pathogen in IP and waterborne infected fish was similar. In both cases the bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Isolation of Vibrio using culture method showed that 64% of the specimens harboured Vibrio strains inside their liver, spleen and kidney. This finding was supported by previous studies which reported that the spleen, liver and kidney are the vital target organs of Vibrio infection (Jun & Woo, 2003;Nelson, Rohovec, & Fryer, 1985).…”
Section: Discussionsupporting
confidence: 86%
“…Isolation of Vibrio using culture method showed that 64% of the specimens harboured Vibrio strains inside their liver, spleen and kidney. This finding was supported by previous studies which reported that the spleen, liver and kidney are the vital target organs of Vibrio infection (Jun & Woo, 2003;Nelson, Rohovec, & Fryer, 1985).…”
Section: Discussionsupporting
confidence: 86%
“…This is in spite of the fact that the branchial surface is largely covered by a simple epithelium and theoretically should be easier to penetrate than the skin which is, histologically, a thicker and a more compact natural obstacle (Evelyn 1996). Consistent with this hypothesis, undamaged gills have been reported to be the entry site for a number of viral and bacterial fish pathogens (Evelyn 1996), including the spring viremia carp virus (Ahne 1978), infectious haematopoietic necrosis virus (Mulcahy et al 1983), Vibrio anguillarum (Nelson et al 1985, Baudin-Laurencin & Germon 1987, Aeromonas salmonicida (Tatner et al 1984) and Pasteurella piscicida (Kawahara et al 1989). …”
Section: Discussionmentioning
confidence: 62%
“…anguillarum [51], suggesting that the peptide is possibly transported towards the infection M A N U S C R I P T…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%